The quality of inclusive education from the perspective of teachers in Poland and Croatia - Žic-Ralić, Anamarija (Array, 2020)
The aim of the study was to explore Croatian and Polish teachers’ opinions on quality of inclusive education. A sample of 173 teachers from Poland and 139 from Croatia completed the Scale on Quality Indicators for Inclusion – for Teachers. In general, teachers reported positive assessments of inclusion quality. Respondents from both countries gave highest ratings on the subscale Support monitoring and evaluation, while the lowest ratings were given on the subscale Teaching assistant support by Polish participants and on the subscale Resources for inclusive education by the Croatian sample. Poland teachers gave higher ratings than Croatian teachers on all the subscales except Teaching assistant support. The discussion makes an attempt to present how two different societal contexts shape the development and implementation of inclusion.